Diş eti kalınlığını artırmak amacıyla injectable-platelet rich fibrinin (I-PRF) ve mikroiğnelemenin kullanılması - ÖZSAĞIR, Zeliha Betü (Bezmialem Vakıf University, 2020)
In this split mouth study, 33 systemically healthy patients with thin gingival biotype were randomly treated with MN+I-PRF, and I-PRF. I-PRF was injected on the one side and MN+I-PRF was performed on the other side of the same patient. Plaque index (PI), gingival index (GI), bleeding on probing (BOP), probing depth (PD), clinical attachment level (CAL), gingival thickness (GT), and keratinized tissue width (KTW) were assesed before the treatment and every month for six months after the final injections.

{{abstract}}
Thesis (dentistry)--Bezmialem Vakıf University, Faculty of Dentistry, department of periodontology, Istanbul
Keywords: Diş Hekimliği = Dentistry; injectable-platelet rich fibrin; Department of Periodontology; Periodontoji = Periodontology; Periodontoloji Anabilim Dalı